Pengembangan Penilaian Berbasis Pendekatan Authentic Inquiry Learning untuk Meningkatkan Motivasi Siswa pada Pelajaran Fisika di SMA Negeri 1 Baturetno Tahun Ajaran 2021/2022 - Aristina, Untoro Adi; Sumardi, Sumardi; Fathoni, Achmad (Universitas Mathla'ul Anwar Banten, 2023)
Research purposes: (1) to describe the characteristics, feasibility, and effectiveness of assessment based on authentic inquiry learning to increase students' motivation in physics lessons at SMA Negeri 1 Baturetno. The research was conducted at SMA Negeri 1 Wonogiri. This research is research and development (Research and development/R&D). Data analysis using quantitative data analysis. The results showed that the characteristics of an assessment based on an authentic inquiry learning approach used an assessment instrument based on an authentic inquiry approach covering 3 (three) aspects, namely attitudes, skills and knowledge. Aspects of attitudes and skills are carried out through performance appraisal using an instrument in the form of a valid observation sheet. Assessment of the knowledge aspect is carried out through tests using multiple choice questions that have been tested for validity, discriminating power, and level of difficulty. The assessment instrument based on authentic inquiry learning that was developed is feasible to be used as an authentic assessment instrument in physics learning. The assessment instrument based on authentic inquiry learning is effective in increasing student learning motivation, as evidenced by the after-before experimental design which shows that the average value of student learning motivation after using an assessment based on authentic inquiry learning is greater than the average value before using an assessment based on authentic inquiry learning.